Relationship between red blood cell transfusion requirements and severity of renal disease during the acute stage of hemolytic uremic syndrome - Cobeñas, Carlos J. (2015)
We performed a retrospective evaluation of patients with diarrhea-associated hemolytic uremic syndrome (D + HUS) with the aims of: (1) determining the rate of red blood cell (RBC) transfusions; (2) establishing the relationship between need for RBC transfusion and severity of renal involvement; (3) determining whether precise measurements of lactic dehydrogenase (LDH) levels can predict the rate of hemolysis and severity of renal disease. A total of 288 patients with D + HUS were retrospectively divided into three groups based on dialysis treatment: group 1, no dialysis treatment (144 patients); group 2, dialysis for 1–10 days (67 patients); group 3, dialysis for ≥11 days (77 patients). Of the patients in groups 1, 2 and 3, 73.6, 86.5 and 83.1 %, respectively, required at least one RBC transfusion. The number of RBC transfusions in groups 1, 2 and 3 was 163, 107 and 162, respectively. Comparison of the groups revealed that the number of RBC transfusions was significantly higher in patients in groups 2 and 3 than in those in group 1 (p = 0.0001). Most RBC transfusions (94.2 %) occurred during the first 2 weeks of the disease. The median peak LDH level was 2091 U/l in 32 patients with no RBC transfusion (group A), 3900 U/l in 73 patients with one transfusion (group B) and 6378 U/l in 62 patients with two or more transfusions (group C). Patients who received two or more RBC transfusions had a significantly higher median peak LDH level than those who did not receive RBC transfusions or received only one transfusion. This difference was also observed between patients who received only one RBC transfusion and those who did not receive any transfusions (p  10 days of dialysis (group 3) had the highest LDH levels, followed by patients with 1–10 days of dialysis (group 2) and then by patients with no dialysis requirements (group 1) (p < 0.00001). The rate of RBC transfusion was higher in patients with the most severe renal injury, and most were performed during the first 2 weeks of the disease. Patients with stable LDH levels seemed to require fewer RBC transfusions. Median peak LDH levels were significantly higher in the group of patients with the most severe renal disease.